Urine Cytology for Detection of Bladder Carcinoma: Experience of Gezira Hospital for Renal Disease and Surgery(GHRDS) - M Omer, Tayseer; M Taha, Sami; Mohammadani, A A; M Ahmed, M El Imam; Elhassan, Moawia M A (Gezira Journal of Health Sciences, 2017)
Background: Urine cytology has been and remains the standard in the initial evaluation of lower urinary tract lesions to rule out bladder cancer. Objectives:   To evaluate the significance of urine cytology as a diagnostic tool for bladder cancer and a to assess the cytological pattern in voided and washed urine. Methodology: This was a cross-sectional descriptive hospital-based study. A total of 43 patients who were suspected to have bladder tumors based on both clinical and radiological findings. Pre-cystoscopy voided urine specimens and post-cystoscopy bladder wash specimens were collected. Three stains were used in preparation of cytological smears Hematoxylin / Eosin, Diff-Quik and May-Grünwald Giemsa, whenever possible equivalent histopathological diagnosis was obtained. Results: This study included 86 urine cytology specimens obtained from a total of 43 cases of suspected bladder cancer. Muscle invasive cases had the higher percentage (37.2%) with more prominent features of malignancy in cytology than the earliest stages. In 30.2% of voided urine specimens were excellent, while 79.1% of bladder wash specimens had excellent quality with more cellularity and preservation of cells in cytological smears . Conclusion: Urine cytology is a reliable method in the diagnosis of bladder cancer. The quality of washed urine is better than voided urine in cytological results.